DATA-DRIVEN EDUCATION: ANALYZING STUDENTS ON THE BASIS OF DATA – IS IT POSSIBLE OR DANGEROUS? - Panjiyeva Gulhayo (Bright Mind Publishing, 2025)
This article analyzes the approach of “data-driven education” based on artificial intelligence — that is, analyzing student activity through data. Although it is possible to monitor aspects such as attendance, grades, participation, and even psychological state of students with the help of AI, this process affects information security and privacy. The article discusses the positive aspects of this technological approach, possible risks, and what ethical and legal criteria should be applied when using this system. As a bonus, the useful or ambiguous aspects of AI systems are also considered through the results of a short observation of real student activity.
Keywords: Data-driven education, artificial intelligence (AI), educational technologies, personalized learning, AI-based assessment, personal data security, algorithmic bias.